Software engineering and formal methods : SEFM 2014 Collocated Workshops: HOFM, SAFOME, OpenCert, MoKMaSD, WS-FMDS, Grenoble, France, September 1-2, 2014 : revised selected papers /: SEFM 2014 Collocated Workshops: HOFM, SAFOME, OpenCert, MoKMaSD, WS-FMDS, Grenoble, France, September 1-2, 2014 : revised selected papers. ([2015]) - Unknown
No abstract available